The Scope of Alliances - Khanna, Tarun (Organization Science, 1998)
We develop the notion that the choice of alliance scope materially affects the character of benefits that alliance participants receive, and thereby affects a range of issues having to do with the initiation, evolution, and termination of the alliance. Indeed, while under-emphasized by academics, determining alliance scope ranks among the most important tasks undertaken by practitioners of alliances. Restricting ourselves to alliances where mutual learning is the primary raison d'être, we first define private benefits as those that accrue to subsets of participants in an alliance, and common benefits as those that accrue collectively to all participants. We demonstrate how the choice of alliance scope affects the mix of private and common benefits, and draw on earlier work to show how this, in turn, affects alliance partners' incentives to invest in learning. As illustrations of the utility of the framework of private and common benefits, we consider two applications. A simple model illustrates the relationship between the choice of alliance scope, the realization of private and common benefits, and the stability, or lack thereof, of the alliance. A second application sheds light on alliance evolution. It examines factors affecting both (a) how a particular alliance evolves, and (b) how firms manage sequences of alliances. Two broader theoretical points also emerge from this discussion of alliance scope. First, we argue that an analytical focus solely on the individual alliance may be inappropriate for studying a wide range of issues. Of the multiple sources of benefits that accrue to alliance participants, there are some whose realization depends on activities in which the firm is engaged, but that may have little to do with the alliance in question. Second, in contrast to much of the literature on alliances, our analysis is based upon the primitives of benefit streams, rather than on transaction cost reasoning. This complementary perspective is better suited to the task of highlighting how activities not governed by an alliance might nonetheless affect multiple aspects of the alliance.